Determining Reference Ranges for Total T4 in Dried Blood Samples for Newborn Screening - Anna-Isabella Hijman; Daniel Konrad; Ralph Fingerhut (MDPI AG, 2020)
The purpose of this study was to define reference intervals for total thyroxine (tT4) in dried blood samples (DBSs) obtained for newborn screening. The aim of our study was to assess the possible benefit of measuring tT4 concentrations directly in DBSs obtained for newborn screening in premature and term-born infants. In order to have a sufficient number of samples for the extremely premature infants (<30 weeks), we set up a retrospective study, measuring the concentrations in DBSs collected over the previous 21 weeks. This time frame was a result of the included miniature study of tT4 stability in DBSs. We found that tT4 strongly correlated with gestational age (GA) in premature infants, highlighting the need for age-specific reference ranges. For term-born infants, the tT4 ranges did not vary significantly among different gestational ages, allowing for the use of one single reference range.